Magnetic resonance imaging evaluation of age and level dependence of multifidus fatty infiltration in normal Indian healthy volunteers - Kamatham, Harshitha; Kadiri, Venkatesh; Muthu, Gautam; Bysani, Swaroop (International Journal of Research in Medical Sciences, 2022)
Background: Multifidus is one of the main stabilizers of lumbar spine. Fatty infiltration of multifidus varies with the age, sex, side and level of spine studied. The present study aims at the evaluation and comparison of the trends of multifidus fatty infiltration in normal population at various levels in both genders, side and different decade groups in healthy individual volunteers. Methods: Twenty-five normal healthy volunteers equally distributed across different age groups (3rd-7th decades) formed the healthy study group. In step 1, normal population magnetic resonance (MR) images are collected and evaluated individually. In step 2, fatty infiltration of all people ascending in age was calculated at each lumbar level and on either side. In step 3, normal population were divided into decades and fatty infiltration at each decade and segment wise comparison was done. In step 4, statistical analysis of significance was done between the groups. All the T2 MR images were measured using Image j 1.50i software. Exclusion criteria included no proper visualization of paraspinal musculature in the T2 MR images. Associated conditions affecting the degeneration (other lytic lesions/vertebral fractures-healed or unhealed). Other etiology included disc prolapse, listhesis, infections, tumors, and trauma. For each MRI scan, at least 3 cuts for each segment were obtained in which the central cut will be selected for measurement. Results: In study population, at all age groups the multifidus fatty infiltration (MFI) at all given levels upper lumbar levels (L1-2, L2-3) showed less fatty infiltration than lower levels. With increasing age there is increase in MFI in all levels. On either side, as the age increases fat % increases and in individual people as the segment going caudal the fat % increases. At each segment left side has more fat % than right side and overall fat % increase from L1 to S1 levels. As decades increases fat % increases in each individual segment, and also fat % increases from cephalad to caudal. There is a rapid increase in fat % transition from 4th to 5th decade. Overall fat % increase is seen from L1 to S1 in each decade. Females L1-2 to L3-4 does not show significant fat % increase. There are more fat % in females than males in lower lumbar levels, but the body mass index (BMI), daily activities may be a confounding factor. Conclusions: Lumbar paravertebral muscle fat content increases with aging, in healthy volunteers 3nd to 7th decade of age. Women, low lumbar levels, left side the multifidus muscle are most affected.